THE EFFECT OF DISTANCE LEARNING IN SHAPING STUDENTS DIGITAL CHARACTER AND SKILLS IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Yuyung, Andi; Sahabuddin, Romansyah; Irfan, Muhammad; Reski, Dwi Pita; Lutfi, Lutfi (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the effect of distance learning on character building and digital skills of students in the era of the Industrial Revolution 4.0, with an emphasis on the challenges faced by students in developing these two aspects. The method used is literature review through analysis of articles relevant to distance learning. The results of the literature analysis show that although distance learning provides wider access to learning resources, there are still significant challenges in terms of students' social interaction and self-discipline that result in the development of their character and digital skills. The significance of these results lies in the importance of appropriate interventions to improve distance learning approaches so as to enhance students' digital character and skills that are indispensable in the competitive world of work. The broader implications of this study suggest that improving the quality of education through distance learning can support the development of qualified human resources to contribute to the advancement of education.